Conflict, contradiction and crisis: an analysis of the politics of AIDS policy in post-Apartheid South Africa - Fletcher, Haley Kim (Rhodes University, Faculty of Humanities, Department of Political Studies, 2009)
Despite the profound impacts of HIV and AIDS on all sectors of South African society, governmental responses to the AIDS epidemic have been inundated with contradiction, conflict and contestation. Though governmental leaders have justified not funding HIV treatment programs because they believe that poverty needs to be dealt with first, social spending has been slashed as part of an adherence to a neo-liberal economic model. Though it would seem that the government would seem to have everything to gain by establishing a cooperative relationship with non-governmental actors regarding the epidemic, the relationship between the government and non-governmental actors has instead been described as nothing short of hostile. Though the government enthusiastically backed Virodene, a supposed treatment for AIDS that turned out to be no more than an industrial solvent, other 'scientifically backed' AIDS treatments have been treated with caution and skepticism "“ to the point where the government even refused to provide funding for programs to prevent mother to child transmission of the virus. And perhaps the most perplexing is that although widely respected for his intellect and cool demeanor, former President Mbeki chose to risk his political career on the AIDS issue by shunning away from the mainstream consensus on the biomedical causes of the epidemic and instead surrounded himself and sought advice from AIDS 'dissidents' This thesis will seek explanations for these apparent contradictions. Using Bourdieu's (1986) typology of capitals, it will build on an argument put forward by Helen Schneider (2002): from the South African government's perspective, the contestation regarding HIV and AIDS policy and implementation is over symbolic capital, or the right to legitimately hold and exercise political power regarding the epidemic. Though this argument helps explain the conflictual relationship between the government and non-governmental actors regarding the AIDS crisis, in order to understand the perplexing contradictions within the governmental policy response, the political context of policy formation must first be taken into consideration.
Keywords: AIDS (Disease) -- Political aspects -- Africa, Southern|AIDS (Disease) -- Political aspects -- South Africa|AIDS (Disease) -- Government policy -- South Africa|Africa -- Politics and government